Perspectives on the mangrove conundrum, land use, and benefits of yield intensification in farmed shrimp production: A review. Issue 1 (11th August 2021) - Boyd, Claude E.; Davis, Robert P.; McNevin, Aaron A.
Abstract: Globally, shrimp farms occupied an estimated 3.490 million hectares (Mha) of land and operated 2.426 Mha of production ponds in 2018. Extensive shrimp farms used 1.804 Mha of farm area (1.377 Mha of production ponds), but produced 11.4% of global shrimp production. An estimated 1.718 Mha of land was required to produce ingredients for feeds used in semi‐intensive and intensive shrimp farming, bringing total land use to 5.160 Mha. Extensive production is located in the intertidal zone and much of this land formerly was or still is in mangrove areas. Expansion of shrimp farms into mangrove areas has slowed. Mangrove areas are inferior sites for shrimp farms, and governments have imposed stricter regulations to protect mangroves. Shrimp farming in mangrove areas is unnecessary to supply the global shrimp demand. Scenarios for increasing global shrimp production without further increase in shrimp farm area are presented. But, if the demand for shrimp continues to increase, it will be impossible to freeze the total land footprint for farmed shrimp, because the land needed for feed presently is roughly equal to the direct land use for shrimp farms. Direct land use for farms can be frozen through greater production pond yields.